2021
DOI: 10.3389/fimmu.2021.685992
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Subtypes and Landscape of Gastric Cancer and to Predict Based on the Whole-Slide Images Using Deep Learning

Abstract: BackgroundGastric cancer (GC) is a highly heterogeneous tumor with different responses to immunotherapy. Identifying immune subtypes and landscape of GC could improve immunotherapeutic strategies.MethodsBased on the abundance of tumor-infiltrating immune cells in GC patients from The Cancer Genome Atlas, we used unsupervised consensus clustering algorithm to identify robust clusters of patients, and assessed their reproducibility in an independent cohort from Gene Expression Omnibus. We further confirmed the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 52 publications
(78 reference statements)
0
27
0
1
Order By: Relevance
“…Not surprisingly, patients with C2 tumors had better prognosis than that of patients with C1 tumors [ 106 ]. Chen et al [ 107 ] classified gastric tumors into three subtypes: i.e., immune subtype 1, 2 and 3, in order to determine the prognosis of gastric cancer patients based on the immune landscape of gastric tumors. They found that patients with immune subtype 3 with a high infiltration of CD8 + and CD4 + -activated T cells, NK cells, and M1 macrophages had the best prognosis, while the patients with immune subtype 1 with a high infiltration B cells, dendritic cells, and CD4 + resting T cells had the worst prognosis of gastric cancer.…”
Section: Molecular Subtypes and Immune Cells In Gastric Cancermentioning
confidence: 99%
“…Not surprisingly, patients with C2 tumors had better prognosis than that of patients with C1 tumors [ 106 ]. Chen et al [ 107 ] classified gastric tumors into three subtypes: i.e., immune subtype 1, 2 and 3, in order to determine the prognosis of gastric cancer patients based on the immune landscape of gastric tumors. They found that patients with immune subtype 3 with a high infiltration of CD8 + and CD4 + -activated T cells, NK cells, and M1 macrophages had the best prognosis, while the patients with immune subtype 1 with a high infiltration B cells, dendritic cells, and CD4 + resting T cells had the worst prognosis of gastric cancer.…”
Section: Molecular Subtypes and Immune Cells In Gastric Cancermentioning
confidence: 99%
“…Inflammation promotes cancer progression primarily by blocking antitumor immunity as well as shaping the tumor microenvironment towards a more favorable tumor cell and by exerting direct signals and tumor promoting functions [ 102 , 103 , 104 ]. Immune system disorders in the course of GC include changes in the microenvironment of the tumor itself as well as immune depletion of T lymphocytes and the involvement of immune checkpoints [ 20 ] ( Figure 7 ).…”
Section: The Role Of Selected Microorganisms and Immunity In The Deve...mentioning
confidence: 99%
“…The likelihood of developing disease in those infected with these microorganisms is largely determined by the long-term inflammatory response that is associated with the virulence of the strains, genetic predisposition of the host, and environmental cofactors. The immune and inflammatory response to H. pylori infection is very important as gastritis may not only lead to further clinical consequences, an ineffective immune response, and increasing inflammation to persistent infection with these bacteria in the body but may also be the cause of the development of oncogenic processes within the stomach [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, other biological factors are also found to be related to the prognosis. Researchers classified the histopathological images based on Human epidermal growth factor receptor 2 (Her2) [ 74 , 75 ], microsatellite instability (MSI) [ 76 ], and immune biomarkers [ 77 , 78 ]. In addition, researchers explored the radiogenomics method to identify the chromosomal instability (CIN) state based on CT images [ 79 ].…”
Section: Ai-assisted Diagnosismentioning
confidence: 99%